A Small‐Molecule "Charge Driver" enables Perovskite Quantum Dot Solar Cells with Efficiency Approaching 13%. Issue 37 (25th July 2019) - Xue, Jingjing; Wang, Rui; Chen, Lan; Nuryyeva, Selbi; Han, Tae‐Hee; Huang, Tianyi; Tan, Shaun; Zhu, Jiahui; Wang, Minhuan; Wang, Zhao‐Kui; Zhang, Chunfeng; Lee, Jin‐Wook; et al.
Abstract: Halide perovskite colloidal quantum dots (CQDs) have recently emerged as a promising candidate for CQD photovoltaics due to their superior optoelectronic properties to conventional chalcogenides CQDs. However, the low charge separation efficiency due to quantum confinement still remains a critical obstacle toward higher‐performance perovskite CQD photovoltaics. Available strategies employed in the conventional CQD devices to enhance the carrier separation, such as the design of type‐Ⅱ core–shell structure and versatile surface modification to tune the electronic properties, are still not applicable to the perovskite CQD system owing to the difficulty in modulating surface ligands and structural integrity. Herein, a facile strategy that takes advantage of conjugated small molecules that provide an additional driving force for effective charge separation in perovskite CQD solar cells is developed. The resulting perovskite CQD solar cell shows a power conversion efficiency approaching 13% with an open‐circuit voltage of 1.10 V, short‐circuit current density of 15.4 mA cm −2, and fill factor of 74.8%, demonstrating the strong potential of this strategy toward achieving high‐performance perovskite CQD solar cells. Abstract : The power conversion efficiency of perovskite colloidal quantum dot (CQD) solar cells is improved using a conjugated small molecule, ITIC. The carrier dynamics of this unique perovskite CQD/ITIC system are investigated, showing an effective carrier transfer from the perovskite CQDs to the ITIC, which provides an additional driving force for charge separation in perovskite CQDs photovoltaic devices and boosts the efficiency up to 12.7%.